Omega-3 supplement use, fish intake, and risk of non-fatal coronary artery disease and ischemic stroke in the Million Veteran Program. Issue 2 (February 2020) - Ward, Rachel E.; Cho, Kelly; Nguyen, Xuan-Mai T.; Vassy, Jason L.; Ho, Yuk-Lam; Quaden, Rachel M.; Gagnon, David R.; Wilson, Peter W.F.; Gaziano, J. Michael; Djoussé, Luc; ,
Summary: Background & aims: Observational and clinical trial evidence suggests an inverse association of omega-3 polyunsaturated fatty acids with coronary artery disease (CAD) mortality, although relationships with non-fatal CAD and stroke are less clear. We investigated whether omega-3 fatty acid supplement use and fish intake were associated with incident non-fatal CAD and ischemic stroke among US Veterans. Methods: The Million Veteran Program (MVP) is an ongoing nation-wide longitudinal cohort study of US Veterans with self-reported survey, biospecimen, and electronic health record data. Regular use of omega-3 supplements (yes/no) and frequency of fish intake within the past year were assessed using a food frequency questionnaire. Cox proportional hazard models were used to estimate hazard ratios (HR) and 95% confidence intervals (CI) for the associations of omega-3 supplement use and fish intake with incident non-fatal CAD and ischemic stroke, defined from electronic health records using validated algorithms. Multivariable models included demographics, body mass index, education, smoking status, alcohol intake, and exercise frequency. Results: Among 197, 761 participants with food frequency data (mean age: 66 ± 12 years, 92% men), 21% regularly took omega-3 supplements and median fish intake was 1 (3–5 ounce) serving/week. Over a median follow-up of 2.9 years for non-fatal CAD and 3.3 years for non-fatal ischemic stroke, we observed 6265 and 4042 incident cases of non-fatal CAD and non-fatal ischemic stroke, respectively. Omega-3 fatty acid supplement use was independently associated with a lower risk of non-fatal ischemic stroke [HR (95% CI): 0.88 (0.81, 0.95)] but not non-fatal CAD [0.99 (0.93, 1.06)]. Fish intake was not independently associated with non-fatal CAD [1.01 (0.94, 1.09) for 1–3 servings/month, 1.03 (0.98, 1.11) for 1 serving/week, 1.02 (0.93, 1.11) for 2–4 servings/week, and 1.15 (0.98, 1.35) for ≥5 servings/week, reference = <1 serving/month, linear p -trend = 0.09] or non-fatal ischemic stroke [0.92 (0.84, 1.00) for 1–3 servings/month, 0.93 (0.85, 1.02) for 1 serving/week, 0.96 (0.86, 1.07) for 2–4 servings/week, and 1.13 (0.93–1.38) for ≥5 servings/week, linear p -trend = 0.16]. Conclusions: Neither omega-3 supplement use, nor fish intake, was associated with non-fatal CAD among US Veterans. While omega-3 supplement use was associated with lower risk of non-fatal ischemic stroke, fish intake was not. Randomized controlled trials are needed to confirm whether omega-3 supplementation is protective against ischemic stroke in a US population.